Consumer behavior in tourism and hospitality research - Woodside, Arch G.; Decrop, Alain (Emerald Publishing Limited, 2017)
This portrait of contemporary tourists proposes that these travelers create consumption audio-portraits and self-explanations (identity constructions) through their purchases and use of travel-related services. Their configurations of destinations, accommodations, travel modes, in-route and destination activities, meal choices, sites/attractions visited, and their travel companions inform others and themselves about who they are. These understandings of self through travel are statements of being - where I've been and what I've done tells me and others who I am. Also, one's definition of self (being) affects tourists' future configurations of travel-related buying and consumption. Thus, tourism-related behavior and being represent virtuous and sometimes vicious consumption systems. Consequently, most tourists are identifiable by who they are and what they know about where they have been and what they have done via their summaries of their trips. The chapters in this volume provide tools and evidence useful for deep understanding of tourists' buying, consumption, and being through examinations of consumer's self-descriptions of personal markers of their trip configurations. This volume's core tenet is that thick descriptions and case-based models are essential steps for highly useful research and deep understanding of tourism behavior.
Prelims -- What can tourists and travel advisors learn from choice overload research? -- From tourism destination to mundane consumption of place: an Asian introspection of France -- Russian Women traveling: a sociocultural perspective -- Gender, age, and education effects on travel-related behavior: reports on Facebook -- The gaze and objectives of townscape visitors -- Experiential context and actual experiences in protected natural parks: comparing France versus Taiwan -- Redirection theory and antisocial travel behavior: configural antecedents to nascent road-road signaling -- Solving the core theoretical issues in consumer behavior in tourism -- Index.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Consumer behavior; Tourists -- Psychology; Tourism; Hospitality industry; Business & Economics -- Marketing -- Research; Tourism industry